Developing a risk-based composite neurologic outcome for a trial of hydroxyurea in young children with sickle cell disease. (February 2019) - Casella, James F; Adams, Robert J; Brambilla, Donald J; Strouse, John J; Maier, Pia; Dlugash, Rachel; Avadhani, Radhika; Vermillion, Krista; Tonascia, James; Voeks, Jenifer H; Hanley, Daniel F; Thompson, Richard E; et al.
Background: Studies of interventions to prevent the many neurological complications of sickle cell disease must take into account multiple outcomes of variable severity, with limited sample size. The goals of the studies presented were to use investigator preferences across outcomes to determine an attitude-based weighting of relevant clinical outcomes and to establish a valid composite outcome for a clinical trial. Methods: In Study 1, investigators were surveyed about their practice regarding hydroxyurea therapy and opinions about outcomes for the "Hydroxyurea to Prevent the Central Nervous System Complications of Sickle Cell Disease Trial" (HU Prevent), and their minimally acceptable relative risk reduction for the two outcome components, motor and neurocognitive deficits. In Study 2, HU Prevent investigators provided overall weights for these two components. In Study 3, they provided more granular rankings, ratings, and maximum number acceptable to harm. A weighted composite outcome, the Stroke Consequences Risk Score, was constructed that incorporates the major neurologic complications of sickle cell disease. The Stroke Consequences Risk Score represents the 3-year risk of suffering the adverse consequences of stroke. In Study 4, the results of the Optimizing Primary Stroke Prevention in Sickle Cell Anemia (STOP2) and Silent Infarct Transfusion Trials were reanalyzed in light of the composite outcome. Results: In total, 22 to 27 investigators participated per study. In Study 1, across three samplings between 2009 and 2015, the average minimally acceptable relative risk reduction ranged from 0.36 to 0.50, at or below the target effect size of 0.50. In 2015, 21 (91%) reported that a placebo-controlled trial is reasonable; 23 (100%), that it is ethical; and 22 (96%), that they would change their practice, if the results of the trial were positive. In Studies 2 and 3, the weight elicited for a cognitive decline (of 10 IQ points) from the overall assessment was 0.67 (and for motor deficit, the complementary 0.33); from ranking, 0.6; from rating, 0.58; and from maximal number acceptable to harm, 0.5. Using data from two major clinical trials, Study 4 demonstrated the same conclusions as the original trials using the Stroke Consequences Risk Score, with smaller p-values for both reanalyses. An assessment of acceptability was performed as well. Conclusion: This set of studies provides the rationale, justification, and validation for the use of a weighted composite outcome and confirms the need for the phase III HU Prevent study. Surveys of investigators in multi-center studies can provide the basis of clinically meaningful outcomes that foster the translation of study results into practice while increasing the efficiency of a study.